Gambaran Acadaemic Self-Efficacy Pada Siswa Sd N X Tamansari, Lelea, Indramayu, Jawa Barat - Shekinah Glory Panjaitan; Agoes Dariyo (LPPM IAINU Kebumen, 2023)
This study aims to describe the academic self-efficacy of students at SDN X Taman Sari, Lelea District, Indramayu Regency, West Java. This research was conducted on 148 male and female students aged 9-13 years from grades 4-6 elementary school. The measuring instrument used in this academic self-efficacy research is part of the measuring instrument for the Faculty of Psychology, Tarumanagara University in 2015 in Indonesian. Through correlation analysis techniques with the SPSS version 25 program. It was found that the dimensions of the highest level were compared to the dimensions of generality and or strength. In addition, based on analysis of additional data, it can be concluded that there are differences in the level of academic self-efficacy in terms of gender.